Spain : Financial Sector Assessment Program; Detailed Assessment of the CPSS-IOSCO Recommendations for the Securities Settlement Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report describes the assessment of the securities clearance and settlement system in Spain, based on the Committee on Payment and Settlement Systems (CPSS)-International Organization of Securities Commissions' (IOSCO) Recommendations for Securities Settlement Systems. It is performed using the CPSS/IOSCO assessment methodology, and assesses the Management Company for Securities Registry, Clearance and Settlement, which operates under the commercial name of Iberclear, a corporation of the Securities Clearance and Settlement Service, SCLV, and the Central Public Registry.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet